Recognition of Japanese university students one year after the discharge of treated water from the Fukushima Daiichi Nuclear Power Station - Hitomi Matsunaga; Isamu Amir; Aizhan Zabirova; Yuya Kashiwazaki; Makiko Orita; Thierry Schneider; Masaharu Tsubokura; Noboru Takamura (PLoS ONE, 2026)
The study clarified the perceptions of the Japanese university students regarding their acceptance of the discharge of treated water (DTW) into the Pacific Ocean approximately a year after the process began. Among the 1453 study participants, 1246 (85.7%) showed DTW acceptability, and 207 (14.3%) were unacceptable. Compared to non-acceptance group, majoring in science, experience collecting information or knowledge about DTW, the ability to explain the difference between contaminated water and treated water, the belief that the Japanese government provides accurate information about DTW, the belief that decision-making of the Japanese public is calm and rational about the DTW, and having no feel reluctant to consume kinds of seafood in Fukushima were independently associated with the acceptance group. Furthermore, the most common way to collect information about DTW was via television or newspapers. The paper suggested that effectively conveying information about DTW to the younger generation is best done passively, such as through TV, street flyers, or Internet advertisements. Participants who had received some kind of information about DTW were more likely to accept DTW than those who had not. The health and environmental effects of DTW from FDNPS are limited; therefore, this complex issue must be dealt with calmly.